Utilization of Liquid Waste from Tofu Production Using Anaerobic Methods for Biogas - Rojali; Suparmin; Desembra Lisa; Indah Restiaty (Gema Lingkungan Kesehatan, 2024)
Liquid waste is a significant problem in environmental control. Waste discharged into water bodies will inevitably pollute the surrounding water body, disrupting the life of living organisms nearby. The tofu industry on Jalan Bangka VII Pela Mampang, Mampang Prapatan Subdistrict, South Jakarta, produces liquid waste collected in waste tanks and discharged directly into water bodies without prior treatment. This causes visible turbidity in the water bodies and foul odors from the tofu industry’s liquid waste, which can disturb nearby residents aesthetically and due to the potential emergence of diseases. Tofu liquid waste can be treated biologically or chemically. Anaerobic biological treatment can be about 70% efficient. This research aims to determine how to treat liquid waste in the tofu industry using a plug-flow reactor. The biogas production methodology involves three stages. Stage I involves preparing a set of biogas digesters. Stage II involves mixing tofu liquid waste and EM4 in a 1:1 weight ratio and placing it in the digester, followed by analyzing the raw materials, including COD, BOD, pH, and acetic acid analysis. Stage III involves a continuous fermentation process in the digester for 60 days with variables including HRT (Hydraulic Retention Time) of 30, 20, and 10 days of operation and temperature control to keep the fermentation conditions constant at 30°C. Therefore, appropriate and effective HRT and OLR (Organic Loading Rate) are needed to produce biogas from tofu liquid waste. In this study, the researcher will use a digester for 60 days to produce biogas from the tofu factory’s liquid waste.